TRADITIONAL CLASSROOM VERSUS 21ST CENTURY CLASSROOM - Gacov, Sanja (International Scientific Journal Vision, 2024)
Modern world trends in education, in response to major socio - economic changes and rapid technical and technological development, have imposed the need for appropriate changes in the organizational setup of the classroom as the basic environment of organized learning. The purpose of these changes is to establish a process of continuous improvement of work in schools, which in turn will lead to quality assurance in education. In this paper, we will look at the classroom as a micro-environment of organized learning from which it is required to adapt and respond to the contemporary level of development, to provide a warm and nice atmosphere and to prepare students who can respond to all the challenges that brings with it new time. Successful teachers are those who have brought their class to a state where they can say, "The students will continue to work on the assigned activities, whether I am with them or not." Maria Montessori